The spatio-temporal influence of atmospheric teleconnection patterns on hydrology in Sweden - Uvo, Cintia B.; Foster, Kean; Olsson, Jonas (Journal of Hydrology: Regional Studies, 2021)
Study region: Sixty-four river gauging stations distributed over Sweden. Study focus: To investigate the influence of climate teleconnection patterns (TP) on streamflow in Sweden. Streamflow data is regionalized and the average hydrographs of each homogeneous region is divided into hydrological seasons. Thereafter the impact of different TPs on the streamflow, per homogeneous region and per hydrological season is analyzed. New hydrological insights for the region: Five homogeneous regions are identified; three located in the north, where snow dominates the hydrological processes, and two located in the south, where rain dominates hydrological processes. The northern hydrographs are separated into three hydrological periods: low streamflow when snow is accumulated, high streamflow during the melting of the snowpack and a transition period in between. The southern hydrographs are characterized by streamflow above the yearly average during the winter and below during the summer. Hydrological periods in different homogeneous regions are influenced by diverse combinations of TPs. Arctic Oscillation, North Atlantic Oscillation and Scandinavian Pattern influence the streamflow in most of the regions during most hydrological periods. The further south and east the region is located, the more TPs influence the streamflow. The resulting streamflow variability is related to the interplay between different TPs both before and during each hydrological period. This interplay may enhance or decrease the individual influence of each TP on streamflow.